2004
DOI: 10.1111/j.1945-5100.2004.tb00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Shocked rocks and impact glasses from the El'gygytgyn impact structure, Russia

Abstract: Abstract-The El'gygytgyn impact structure is about 18 km in diameter and is located in the central part of Chukotka, arctic Russia. The crater was formed in volcanic rock strata of Cretaceous age, which include lava and tuffs of rhyolites, dacites, and andesites. A mid-Pliocene age of the crater was previously determined by fission track (3.45 ± 0.15 Ma) and 40 Ar/ 39 Ar dating (3.58 ± 0.04 Ma). The ejecta layer around the crater is completely eroded. Shock-metamorphosed volcanic rocks, impact melt rocks, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
142
1
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(173 citation statements)
references
References 16 publications
(22 reference statements)
18
142
1
12
Order By: Relevance
“…The shock-induced changes observed in porphyritic volcanic rocks from El´gygytgyn can be applied to a general classification of shock metamorphism of siliceous volcanic rocks. That El´gygytgyn is an impact crater was confirmed in the late 1970s by Gurov and co-workers (Gurov et al, 1978(Gurov et al, , 2007Gurov and Koeberl, 2004), who found shocked minerals and impact glasses in samples at the crater. However, the impact rocks on the surface have been almost totally removed by erosion, and so the El´gygytgyn Drilling Project provides the unique opportunity to study the crater-fill impactites in situ and determine their relations and succession.…”
Section: Impact Rocksmentioning
confidence: 56%
“…The shock-induced changes observed in porphyritic volcanic rocks from El´gygytgyn can be applied to a general classification of shock metamorphism of siliceous volcanic rocks. That El´gygytgyn is an impact crater was confirmed in the late 1970s by Gurov and co-workers (Gurov et al, 1978(Gurov et al, , 2007Gurov and Koeberl, 2004), who found shocked minerals and impact glasses in samples at the crater. However, the impact rocks on the surface have been almost totally removed by erosion, and so the El´gygytgyn Drilling Project provides the unique opportunity to study the crater-fill impactites in situ and determine their relations and succession.…”
Section: Impact Rocksmentioning
confidence: 56%
“…The circular-shaped impact crater has a diameter of 18 km and was formed in Cretaceous volcanic rocks, such as rhyolitic and dacitic lavas, tuffs and ignimbrites as well as andesites and tuffs of andesitic composition (Gurov and Koeberl, 2004). The highlands at the crater rim today have heights between 50 and 430 m above lake level.…”
Section: Prerequisite Site Informationmentioning
confidence: 99%
“…Although the remnants of ejecta around the structure are completely eroded, El'gygytgyn crater is one of the better preserved impact structures on Earth (Dietz and McHone 1976;Layer 2000;Gurov and Koeberl 2004;Gebhardt et al 2006). Its surface expression in space images has been described as "excellent" (Garvin and Grieve 1986;Grieve et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A classification of shock-metamorphosed siliceous volcanic rocks was proposed for shock pressures up to 55 GPa Gurova 1979, 1991;Gurov and Koeberl 2004;Gurov et al 2005). The high-pressure quartz polymorphs stishovite and coesite were detected in quartz from strongly shocked rhyolites and rhyolitic tuffs (Gurov and Gurova 1991;Gurov and Koeberl 2004).…”
Section: Introductionmentioning
confidence: 99%